Validity, Reliability, and Practicality of a Ten-Minute Geriatric Assessment in Primary Care Patients - Piti, Phatchanit; Wiriya, Bongkot; Kraikaitsakul, Thiwarut; Muangpaisan, Weerasak; Suraseranivongse, Suwannee (Journal of Primary Care and Family Medicine (PCFM), 2025)
Background: The Comprehensive Geriatric Assessment (CGA) is not practical in the community. The ten-minute WHO geriatric assessment tool was designed for screening purposes. The objective of this study was to cross-validate two geriatric assessments in terms of content validity, concurrent validity, interrater reliability, and practicality. Methods: A Ten-minute WHO geriatric assessment tool was translated and tested for content validity. Concurrent validity was tested by agreement with the CGA in 112 patients, aged 60 years. Interrater reliability and practicality of the ten-minute WHO geriatric assessment were tested in four primary care nurses. Results: Moderate agreement (kappa > 0.4) was found in four conditions, including urinary incontinence, depression, immobility, and hearing (kappa 0.780, 0.762, 0.573, and 0.519, respectively). Another four conditions had poor agreement, including memory, falls, nutrition, and vision (kappa 0.091, 0.026, 0.019, and 0.219, respectively). Interrater reliability was excellent (agreement 100%). Regarding content validity, the indices of item-objective congruence are > 0.5 in all items, but the content validity index is 0.75. Practicality was good based on the short duration of rating, and feasible for clinical use. Conclusion: Interrater reliability and practicality of the ten-minute WHO geriatric assessment tool were good to excellent. Content validity was moderate to acceptable. Concurrent validity compared with the comprehensive geriatric assessment tool yielded fair results. Keywords: validity, agreement, geriatric assessment, ten-minute geriatric assessment